Intraneural ganglion cyst: a case report and a review of the literature - Lisovski, Vladislav; Minderis, Mindaugas (Acta medica Lituanica, 2019)
Background. An intraneural ganglion cyst is a non-neoplastic gelatinous cyst, which can be found within the epineurium of a peripheral nerve and lead to signs and symptoms of peripheral neuropathy. Early diagnosis and appropriate surgical treatment of this condition is a key to a successful outcome. Materials and methods. We describe a case of a patient with peroneal nerve neuropathy caused by an intraneural ganglion cyst. Postsurgically, only partial relieve of the symptoms was achieved because of delayed diagnosis. Results and conclusions. The aetiology of intraneural ganglia is controversial and historically different pathogeneses of this condition have been described. Diagnosis of these cysts is based on MRI. Multiple surgical treatment strategies have been developed based on different pathogenesis of the formation of these cysts, but neuropathy is reversible only, if this condition is diagnosed and treated early.